Trends in colorectal cancer surgical resection rates during the screening era: a retrospective study in Italy - Manuel Zorzi; Carmen Stocco; Stefano Guzzinati; Marta Sbaraglia; Silvia Rizzato; Salvatore Pucciarelli; Nicola Gennaro; Lucia Calciano; Gaya Spolverato; Laura Memo; Emanuele D L Urso; Silvia Negro (BMJ Open Gastroenterology)
Background Faecal immunochemical test (FIT)-based screening is effective in reducing colorectal cancer (CRC) incidence, but its sensitivity for proximal lesions remains low.Objectives We compared age-adjusted CRC surgical resection rates across anatomic sites (proximal colon, distal colon, rectum), age groups and sex over 20 years in a large Italian population. We particularly focused on changes in trends following FIT-screening implementation in the target population (50–69 years).Design This retrospective study analysed data from the Veneto Region’s administrative Hospital Discharge Dataset, involving over 54 000 patients aged 40–89 (43.4% female) who underwent CRC surgery between 2002 and 2021.Results Overall, surgery rates increased until 2007 (annual percentage changes: 2.5% in males, 2.9% in females) and then declined (−4.2% in males, −3.4% in females). This decline was steeper for distal and rectal cancers compared with proximal cancer, suggesting a shift towards more right-sided CRC surgery.In males, the prescreening increase in proximal surgery was reversed after screening implementation (slope change: −6%) while the prescreening decline accelerated for distal (−4%) and rectal (−3%) surgeries. In females, stable prescreening trends shifted downward for all sites (−5% for proximal, −8% for distal and −7% for rectal surgery). However, the change in trends between prescreening and postscreening periods was not different across anatomic sites for either sex (all slope change differences in pairwise comparisons were not statistically significant).Conclusion The shift towards proximal surgery may not be entirely due to the FIT’s low sensitivity but may reflect an underlying upward trend in proximal cancers independent of screening.